(untitled) (MAUSAM, 1982)
Meteorological analysis or stem-borer attack on paddy crop at Pattambi (Kerala State) shows that both in pre-sowing season and the actual crop season, temperature, relative humidity and sunshine hours at some critical periods account for most or the variations in the percentage of infestation, Thus forewarning or the stem-borer attack on paddy crop at Pattambi from weather data appears feasible.